Political Participation and Research Motivation of Iran Specialists in American Academia: How an Academic Community Responds to Events in the U.S. and Iran (Higher Education Politics and Economics, 2026)
We report results from a longitudinal study of political participation among Iranian Studies scholars working in U.S. academia. Qualtrics surveys of Iranian Studies specialists were conducted in 2016 and 2023, the surveys featuring questions about reported political activities such as voting, contacting public officials, signing petitions, and participating in demonstrations. The surveys also included questions about media outreach and interactions with journalists. Iranian Studies scholars reported very high levels of political activity, exceeding those found in previous studies of political participation among academics. In several instances participation levels increased from 2016 to 2023. We believe that these high levels of political participation are a response to political developments in Iran and the United States, including Women.Life.Freedom, the Trump travel ban, and ongoing tensions in US-Iran relations.   Our findings suggest that studies of academic political behavior should account for the political pressures that can influence specific subfields in distinctive ways.